2001
DOI: 10.1002/tera.1073
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of first‐year survival among infants with selected congenital anomalies in Texas, 1995–1997

Abstract: Overall, first-year survival for infants with congenital anomalies was high. Additional population-based studies are needed to quantify improvements in first-year survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
96
6
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(113 citation statements)
references
References 23 publications
10
96
6
1
Order By: Relevance
“…This effect of multiple congenital anomalies on survival has been described in other population-based studies of birth defects. 2,8,15,16 Racial/ethnic disparities in survival were found in the present study, as reported by others. After multivariable adjustment, NH blacks with functional single ventricle had a 41% greater risk of death compared with NH whites.…”
Section: Fixler Et Al Five-year Mortality Of Functional Single Ventriclesupporting
confidence: 90%
See 1 more Smart Citation
“…This effect of multiple congenital anomalies on survival has been described in other population-based studies of birth defects. 2,8,15,16 Racial/ethnic disparities in survival were found in the present study, as reported by others. After multivariable adjustment, NH blacks with functional single ventricle had a 41% greater risk of death compared with NH whites.…”
Section: Fixler Et Al Five-year Mortality Of Functional Single Ventriclesupporting
confidence: 90%
“…Nevertheless, patients with hypoplastic left heart syndrome (HLHS) and single ventricle did not show evidence for improvement in outcome. In 2001, Nembhard et al 8 reported first-year survival among infants with congenital anomalies in Texas born between 1995 and 1997. This population-based registry study showed that 1-year survival was lower for HLHS (20.9%) than for all other birth defects studied except anencephaly.…”
mentioning
confidence: 99%
“…This is due primarily to congenital heart disease, which affects half of all children with DS (Halliday et al 1995;Morris et al 1999;Nembhard et al 2001;Frid et al 2004). Despite advances in neonatal care, DS survival is only 90-95% at 1 year and between 85 and 90% at 10 years (Leonard et al 2000;Forrester and Merz 2002;Glasson et al 2002;Bell et al 2003;Frid et al 2004;Marino et al 2004).…”
Section: Own Syndrome (Ds) Is Caused By Trisomy 21 Andmentioning
confidence: 99%
“…Patients with trisomy 18 have prenatal-onset severe growth retardation, characteristic craniofacial features, various visceral and skeletal malformations, and significant psychomotor mental retardation [Carey, 2001]. Several populationbased studies showed a remarkably reduced lifespan, with survival rates at age 1 year from 0 to 10% and with median survival time from 3 to 14.5 days [Carter et al, 1985;Young et al, 1986;Goldstein and Nielsen, 1988;Root and Carey, 1994;Embleton et al, 1996;Naguib et al, 1999;Nembhard et al, 2001;Brewer et al, 2002;Rasmussen et al, 2003]. The major causes of death were reported to be apnea and withdrawal of treatment [Embleton et al, 1996], and the presence of a congenital heart defect did not seem be associated with early death [Embleton et al, 1996;Rasmussen et al, 2003].…”
Section: Introductionmentioning
confidence: 99%